Pengaruh Budaya Organisasi terhadap Produktivitas Kerja Pegawai di Pemerintah Daerah - Lili Indrawati; Etti Ernita Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to examine the influence of organizational culture on employee working productivity. The organizational culture tested is a bureaucratic culture, to determine the extent to which employees apply this culture in increasing their working productivity. The sample of this study was taken from 27 working units of local government offices in West Bandung Local Government. The researcher collected data by distributing questionnaires of 4 copies each to the 27 working units of local government offices in West Bandung Local Government. Research respondents are financial managers from the working units. The data analysis tool used is simple regression. The results of the study indicate that organizational culture has a significant positive effect on the working productivity of the local government employees in West Bandung Local Government.